1999
DOI: 10.1007/s004210050559
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate can be used as an ergogenic aid in high-intensity, competitive cycle ergometry of 1 h duration

Abstract: The aim of this study was to determine whether a dose of 300-mg x kg(-1) body mass of sodium bicarbonate would effect a high-intensity, 1-h maximal cycle ergometer effort. Ten male, well-trained [maximum oxygen consumption 67.3 (3.3) ml x kg(-1) x min(-1), mean (SD)] volunteer cyclists acted as subjects. Each undertook either a control (C), placebo (P), or experimental (E) ride in a random, double-blind fashion on a modified, air-braked cycle ergometer, attached to a personal computer to which the work and pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 45 publications
5
58
1
2
Order By: Relevance
“…Neither is it possible to predict maximum pH values on the basis of body weight. As has been seen previously 20,21,44 , responses to the same dose of are varied with respect to changes in pH even when resting pH values are almost identical.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Neither is it possible to predict maximum pH values on the basis of body weight. As has been seen previously 20,21,44 , responses to the same dose of are varied with respect to changes in pH even when resting pH values are almost identical.…”
Section: Discussionsupporting
confidence: 57%
“…This suggests that when used as an ergogenic aid to improve sprint performance, in studies that have either used 60 min after ingestion 23,35 or 90 min post ingestion 20,21,44 , the time lag is probably too short (60 min) or too long respectively. This is supported by the fact that the mean time to peak pH, across all participants is 65.0±18.4 min, confirming that an exercise time of 60-90 min post ingestion is either too short, or too long respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by McNaughton et al [14] have also found that sodium bicarbonate can be used as an ergogenic aid to offset the fatigue process in high-intensity, competitive cycle ergometry of 1 hour duration.…”
Section: Evidences For Improvement In Performancementioning
confidence: 99%
“…Daneben lässt sich bei Wettkampfs p o rt l e rn in bestimmten Disziplinen d u r ch Alkalisierung eine Steigerung der Leistungsfähigkeit erreichen [10,11].…”
Section: Funktionelle Medizin Und Klinische Aspekteunclassified